Comparative Analysis on Corporate Disclosure Practices of Listed Companies in ASEAN-5 after the Adoption of the Renewal Regional Disclosure Standards - Nunthapin Chantachaimongkol; Shuwen Chen (STIE Malangkucecwara, 2019)
This study aims to assess and compare the extent of corporate disclosure of the countries that have already implemented the renewal ASEAN disclosure standards with the countries that have not implemented yet. The empirical result indicates that overall picture of corporate disclosure in the ASEAN is in a good progression, with an increasing trend. Then, an independent t-test analysis addresses that the renewal ASEAN disclosure standards could have an effect on the level of corporate disclosure, especially in terms of non-financial and strategic information. But, it has no impacts on financial information. Therefore, it can be concluded that the regional disclosure standards might be one of the supportive factors for enforcing businesses to disclose more corporate information to the public. With this finding, it could alert regional regulators by providing the weaknesses of the current activities related to economic integration and guiding the direction for further development.